A Rare Urologic Emergency of Penile Strangulation with a Metallic Ring - TİNAY, İLKER (GALENOS YAYINCILIK, 2017)
A 31-year-old man was presented to our emergency room in a distressed state with a heavy metallic ring 4 cm wide and 0.6 cm thick placed at the root of the penis for attempting masturbation. The ring was placed approximately 6 hours previously and the patient had tried several maneuvers using different tools to remove it. The patient suffered proximal penile strangulation with painful priapism. Under general anesthesia, multiple punctures to the glans penis and circumcision scar were made in order to aspirate entrapped blood and edema. After minimal regression of distal penile edema, we tried to cut the ring with metal cutters that orthopedicians use, but it was not successful. With a quite amount of lubricant, surgery string to keep the distal penis compressed, and the application of steady force to the ring, we were able to remove the metallic ring. The operation time was 2 hours without any complications. At 36 hours after the operation, the penis looked quite normal and the patient was discharged after 48 hours. The urethral catheter was removed at the first week after the operation. At the end of 12 months, there were no findings of urethral stricture and erectile dysfunction.
Keywords: Emergency; metalic ring; penile strangulation; INCARCERATION